2011
DOI: 10.1038/aps.2010.223
|View full text |Cite
|
Sign up to set email alerts
|

The role of Med19 in the proliferation and tumorigenesis of human hepatocellular carcinoma cells

Abstract: In addition, the ability of the Med19-RNAi-Lentivirus vector-infected Hep3B cells to form tumors after inoculation into nude mice was determined. Results: Recombinant lentiviral vectors expressing small interfering RNA (siRNA) against Med19 were constructed and were found to efficiently downregulate Med19 mRNA and protein levels in HepG2 and Hep3B cells. Furthermore, the inhibition of Med19 by RNAi dramatically reduced hepatocellular carcinoma cell proliferation, induced cell-cycle arrest in the G 0 /G 1 phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Furthermore, infection of lentivirus containing shRNA targeting MED19 resulted in lower colony formation ability and attenuated tumor formation and growth in PC-3 xenografts. This in vivo result provided new support for the role of MED19 in promoting neoplasia, which support the results of previous studies that reported an induction of tumorigenesis in hepatocellular carcinoma and lung cancer cells treated with MED19 siRNAs (14,15). Together, these findings justified the potential usefulness of MED19 as a prostate cancer biomarker.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, infection of lentivirus containing shRNA targeting MED19 resulted in lower colony formation ability and attenuated tumor formation and growth in PC-3 xenografts. This in vivo result provided new support for the role of MED19 in promoting neoplasia, which support the results of previous studies that reported an induction of tumorigenesis in hepatocellular carcinoma and lung cancer cells treated with MED19 siRNAs (14,15). Together, these findings justified the potential usefulness of MED19 as a prostate cancer biomarker.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results have been obtained in the previous study. The suppression of Med19 results in an impaired cell proliferation in colonic, hepatic, lung, pancreatic, bladder, prostate, breast carcinoma, and osteosarcoma (Cui et al, 2011;Ji-Fu et al, 2011;Li et al, 2011aLi et al, , 2011bSun et al, 2011;Wang et al, 2011;Zhang et al, 2011;Zou et al, 2011). Collectively, the results presented in this paper, together with the previous reports, provide solid evidences for the involvement of Med19 in the development of malignancy.…”
Section: Discussionsupporting
confidence: 79%
“…In lung cancer, MED19 could promote tumor proliferation, tumorigenesis, metastasis, and enhance chemo-sensitivity to cisplatin in non-small cell lung cancer cells [ 14 16 ]. The Med19 has been reported to promote tumor growth and/or metastasis in ovarian cancer, gastric cancer, pancreatic cancer, osteosarcoma, and liver cancer [ 5 7 , 17 18 ]. However, there are few reports about the roles of Med19 in PCa.…”
Section: Discussionmentioning
confidence: 99%